Catalytic Dehydrogenation and Cracking of Cyclohexane over Ni/AlO Solids - E.A. Sultan; A.S. Ahmad; G.A. El-Shobaky; S. Ayad (Adsorption Science & Technology, 1995)
The catalytic conversion of cyclohexane over Ni/Al 2 O 3 has been investigated using a microcatalytic pulse technique. The nickel content was varied between 7.9–34.3 wt.% NiO and the reaction temperatures were changed between 240–450°C. The liquids and gases produced were analyzed chromatographically. The results obtained reveal that the cyclohexane underwent both dehydrogenation and cracking reactions producing benzene and light aliphatic hydrocarbons, respectively. The nickel metal acts as the actual active constituent of Ni/Al 2 O 3 catalysts. The selectivity towards the cracking reaction was increased by increasing the amount of nickel, the solids possessing 7.9 wt.% Ni showing no detectable cracking activity at temperatures below 350°C. On the other hand, the selectivity towards benzene formation decreased on increasing the extent of nickel in the various solid catalysts. Although catalysts containing 7.9 wt.% nickel showed the smallest catalytic activity, they exhibited the highest selectivity towards benzene formation.